(untitled) (Medical Forum Monthly, 2024)
platelets transfusion in patients with dengue fever in our community hospitals. Place and duration of study: This study was done from 1st, September 2010 to 15th, November 2010 in three different hospitals, two were urban and one was rural and all three were tertiary care hospitals. Materials and methods: Our study was based on 200 patients who were serologically confirmed cases for Dengue fever (IgM +ive) and had symptoms and signs of dengue fever for more than four to seven days at the time of admission. Clinical data reports of hematological investigations, platelets requirements, and data obtained from daily follow up, were analyzed. Results: There were 200 serologically confirmed Dengue fever patients, among them 176 were males, 24 females, 183 patients were urban and 17 were rural patients. Thrombocytopenia was found in 174 (87%) on the day of admission. Among them 48 (24%) patients had platelets count in between 20,000 to 40,000/cumm, 46 (23%) had platelets count <20,000/cumm, and 4 (2%) had platelets count <10,000/cumm. Patients having platelets count < 20,000/cumm all have hemorrhage manifestations. Out of 48 (24%) patients having platelets count in between 20,000 to 40,000/cumm, 21(43%) had hemorrhagic manifestations. 98(49%) patients were given platelets transfusion. None of these patients got platelets transfusion with platelets count above 40,000/cumm. 27 patients received platelets therapy inappropriately (platelets count < 40,000/cumm with no hemorrhagic manifestations. There was only 2 mortality in these patients. Conclusion: Our study suggests that bleeding occurs more often in patients with severe thrombocytopenia (platelets count <20,000/cumm) and these patients need urgent platelets transfusion. Patients having platelets count in between 20,000-40,000/cumm are at moderate risk and these patients require platelets transfusion if they have hemorrhagic manifestation. Platelets count above 40,000/cumm are at low risk and no need of platelets transfusion in these patients, only these patients need careful monitoring.